Pengaruh Kompetensi Kerja Dan Lingkungan Kerja Terhadap Kinerja Personil Dengan Motivasi Kerja Sebagai Variabel Intervening Pada Yanma Polda Sumbar - Salsabila Silvia Alwis; Vivi Nila Sari; Nia Nadilla (CV. ITTC INDONESIA, 2026)
This study aims to analyze the influence of work competence and the work environment on personnel performance, with work motivation as an intervening variable at the West Sumatra Regional Police's Human Resources Development Agency (Yanma Polda Sumbar). This study used a quantitative approach with a survey method by distributing questionnaires to personnel as respondents. The sampling technique used proportional sampling, while data analysis used path analysis based on Partial Least Squares (PLS). The results showed that work competence and the work environment have a positive and significant influence on work motivation. In relation to performance, work competence, the work environment, and work motivation were proven to have a positive and significant influence on personnel performance. Intervening variable analysis showed that work motivation significantly mediated the influence of the work environment on personnel performance. However, work motivation was found to be unable to significantly mediate the influence of work competence on personnel performance. These findings have implications for the management of the West Sumatra Regional Police's Human Resources Development Agency (Yanma Polda Sumbar) to prioritize increasing motivation through improving the work environment to achieve higher performance standards, while continuously improving personnel competence.